2019
DOI: 10.15517/rbt.v67i4.34793
|View full text |Cite
|
Sign up to set email alerts
|

Cuantificación de hormonas 17β - estradiol y progesterona en el caracol rosa Lobatus gigas (Mollusca, Gastropoda)

Abstract: Las hormonas sexuales son responsables del mantenimiento de los caracteres sexuales, maduración de gametos y del comportamiento sexual en vertebrados y algunos invertebrados. Lobatus gigas es un gasterópodo de importancia económica y ecológica del Caribe, para el cual pocos han sido los estudios de su reproducción en cautiverio y de la influencia de hormonas en el proceso.  El objetivo de este trabajo fue determinar la presencia de estrógeno y progesterona en L. gigas y comparar las concentraciones de estas ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…As such, the number of eggs laid would be an underestimate relative to many areas where the spawning season is more protracted. Simulating only the peak spawning season avoided the need to parameterize increasing concentrations of sex hormones and associated rates of oogenesis with the progression of the spawning season [42] or changes in density and movement rates associated with the formation and dissolution of the aggregation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, the number of eggs laid would be an underestimate relative to many areas where the spawning season is more protracted. Simulating only the peak spawning season avoided the need to parameterize increasing concentrations of sex hormones and associated rates of oogenesis with the progression of the spawning season [42] or changes in density and movement rates associated with the formation and dissolution of the aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…This article is a US Government work. It is not subject to copyright under 17 USC 105 parameterize increasing concentrations of sex hormones and associated rates of oogenesis with the progression of the spawning season [42] or changes in density and movement rates associated with the formation and dissolution of the aggregation. This model may also be useful for identifying reference points that avoid recruitment failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(c) Quantification of sex steroids in gonads Variations in the reproductive development of mollusks can be evaluated by measuring the levels of steroids (e.g., estradiol and progesterone), as several studies have shown that these hormones play a role in the regulation of invertebrate reproduction processes (Wang and Croll, 2004;Gauthier-Clerc et al, 2006;Croll and Wang, 2007;Lafont and Mathieu, 2007;Chong et al, 2019). The gonad of 20 female F. crassa individuals was carefully examined under a stereomicroscope to confirm the presence and quantity of parasites.…”
Section: Histological and Biochemical Analysis Of Parasitized And Non...mentioning
confidence: 99%